Multi-Parental Populations Suitable for Identifying Sources of Resistance to Powdery Mildew in Winter Wheat - Nordestgaard, Nana Vagndorf; Thach, Tine; Sarup, Pernille; Rodriguez-Algaba, Julian; Andersen, Jeppe Reitan; Hovmøller, Mogens Støvring; Jahoor, Ahmed; Jørgensen, Lise Nistrup; Orabi, Jihad (Frontiers in Plant Science, 2021)
Wheat (Triticum aestivum L.) is one of the worlds staple food crops and one of the most devastating foliar diseases attacking wheat is powdery mildew (PM). In Denmark only a few specific fungicides are available for controlling PM and the use of resistant cultivars is often recommended. In this study, two Chinese wheat landraces and two synthetic hexaploid wheat lines were used as donors for creating four multi-parental populations with a total of 717 individual lines to identify new powdery mildew resistance genetic variants. These lines and the nine parental lines (including the elite cultivars used to create the populations) were genotyped using a 20K Illumina SNP chip, which resulted in 8902 segregating single nucleotide polymorphisms for assessment of the population structure and whole genome association study. The largest genetic difference among the lines was between the donors and the elite cultivars, the second largest genetic difference was between the different donors; a difference that was also reflected in differences between the four multi-parental populations. The 726 lines were phenotyped for powdery mildew resistance in 2017 and 2018. A high PM disease pressure was observed in both seasons, with severities ranging from 0 to > 50%. Whole genome association studies for genetic variation in PM resistance in the populations revealed significant markers mapped to either chromosome 2A, 2B or 2D in each of the four populations. However, linkage disequilibrium between these putative quantitative trait loci (QTL) were all above 0.80, probably representing a single QTL. A combined analysis of all the populations confirmed this result and the most associated marker explained 42% of the variation in PM resistance. This study gives both knowledge about the resistance as well as molecular tools and plant material that can be utilised in marker-assisted selection. Additionally, the four populations produced in this study are highly suitable for association studies of other traits than PM resistance.